Impact of Quality Life Work and Workload On Employee Performance at PT. BRI Tbk Barru Branch Office - Muh. Agil Saputro; asdi, Asdi; Sitti Marhumi (CV. AFDIFAL MAJU BERKAH, 2024)
Research purposes This For know influence quality life work and burden Work to performance employees at PT. Bank Rakyat Indonesia Tbk . Barru Branch Office. Type of data used in study This is the quantitative data obtained from distributed and related questionnaires​ with the problem under study . Data collection techniques were carried out with observation and sharing questionnaire . In research This data sources used in Data collection includes primary data and secondary data . Instrument research used​ in study This use method scale likert . Based on results data research with use calculation statistics through Statistics for the Social Science (SPSS) version 21 application regarding influence quality life work and burden Work to performance employees at PT. Bank Rakyat Indonesia Tbk . Barru Branch Office which has discussed in chapter before , then writer interesting A conclusion important that is quality life work and burden Work influential positive and significant to performance employee proven with efficient regression quality life work (X 1 ) of 0.300 and load work (X 2 ) of 0.510 and value t count (X 1 ) is 2.020 > t table 2.00 with mark significance 0.047 <0.05 whereas mark t count (X 2 ) is 3,862 > t table 2.00 with mark significance 0.000 < 0.05.